Експрес-метод оцінювання фінансової стійкості банку - Дробязко, А.О.; Любіч, О.О. (Математичне моделювання в економіці, 2019)
Метою статті є пропозиція застосування набору фінансових моделей для прогнозування короткострокової фінансової стійкості банків на основі доступної інформації з відкритих джерел про баланси банків. The aim of this work is a visualization of imbalances of financial flows in bank's activity on the basis of mathematical models based on accessible to the general public the banking balance statistics and identification of risks. Market monitoring with consistent usage of the proposed article four models for quality evaluation of bank balance sheets allows you to have tools for adequate risk assessment of short-term investments. The method of assessing the financial status of banks enables to provide a clear and vivid interpretation of managerial decisions on the possibility of cooperation (opening of limits) with market contractors on the basis of available and sometimes deliberately distorted information.